Complete IELTS : - Wyatt, Rawdon (Cambridge University Press, 2012)
Combines the very best in contemporary classroom practice with stimulating topics aimed at young adults. It is designed to introduce students to the critical thinking required for IELTS and provide strategies and skills to maximise their score in all parts of the test.